Blocking Conceptualization - Barney G. Glaser (Grounded Theory Review: An International Journal, 2011)
Generating good GT conceptual ideas requires the researcher to be a non citizen for the moments of research so he can come closer to letting the data speak for itself. He/she needs to be free for the research of the normal issue orientations of everyday life so he/she must limit normal citizen bias. Suspending issues of gender, age, color, religion, nationality etc. are important. Therefore to avoid this kind of block the researcher should not get into a study when he/she cannot handle the issue as data impartially; not handle as neither right nor wrong. Gender studies are particularly sensitive and hard to avoid strong bias orientations. Face sheet data has to emerge as relevant, and often none do. They cannot be assumed as in QDA. So many GT studies have nothing to do with face sheet data.